Microbial Type I Fatty Acid Synthases (FAS): Major Players in a Network of Cellular FAS Systems - Schweizer, Eckhart; Hofmann, Jörg (Microbiology and Molecular Biology Reviews, 2004)
Article Usage Stats Services MMBR Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue MMBR About MMBR Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy MMBR RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1092-2172 Online ISSN: 1098-5557 Copyright © 2014 by the American Society for Microbiology. For an alternate route to MMBR .asm.org, visit: MMBR